Longitudinal analysis of Covid-19 infection trends and in-hospital mortality across six pandemic waves in Tunisia - Manel Ben Fredj; Amel Gara; Meriem Kacem; Wafa Dhouib; Donia Ben Hassine; Cyrine Bennasrallah; Imen Zemni; Nissaf Ben Alaya; Sondes Derouiche; Amani Maatouk; Ines Bouanene; Hela Abroug; et al. (Archives of Public Health)
Abstract Background The global impact of the COVID-19 pandemic was remarkably diverse, unfolding with multiple waves that have touched countries and continents in distinctive ways, leading to varying rates of mortality. The objectives of this study were to examine the characteristics and in-hospital fatality rates of COVID-19 patients hospitalized in the Monastir governorate over two years, with an overall analysis and a wave-specific breakdown throughout the pandemic's progression. Methods We carried out a two-year longitudinal study, enrolling all COVID-19-infected patients admitted to both public and private health facilities in the governorate of Monastir from March 2020 to March 2022. The study covered six complete infection waves. Patients were followed from their first day of admission to their outcome in hospital. The data were collected using a questionnaire manually completed by well-trained residents. The data were globally analyzed across all hospitalized patients and then compared based on the different waves. Results Overall, 5176 were hospitalized. The cumulative in-hospital case fatality rate (CFR) over the study period was 21.4%. After the first wave (W1), the in-hospital CFR followed a gradual increase, reaching its peak at 27.5% during W4 (alpha variant). Later, it decreased to 21.8% during W5 (delta variant), and further declined to 19.5% during W6, associated with the Omicron variant (overall p < 0.001). W5 exhibited the highest proportions of infections, hospitalizations, and in-hospital deaths. W6 featured a low hospitalization rate of 2.8% and a decline in severe cases. Nevertheless, there was a significant surge in hospitalizations among both the pediatric (≤ 18 years) and geriatric (≥ 75 years) populations, with a pronounced impact on the elderly with chronic conditions. This surge resulted in an increase in fatalities among the elderly. The length of stay (LoS) decreased throughout the course of the pandemic, declining from 13 days [10;14] in W1 to 4 days [2;9] in W6 with almost half of them had a LoS less than seven days (55.6%). Conclusion This study underscores the critical interplay of variant-specific disease severity, patient demographics, and evolving healthcare responses in managing COVID-19's impact on hospital outcomes.